2014
DOI: 10.1136/bmjopen-2013-003713
|View full text |Cite
|
Sign up to set email alerts
|

The completeness of intervention descriptions in published National Institute of Health Research HTA-funded trials: a cross-sectional study

Abstract: ObjectivesThe objective of this study was to assess whether National Institute of Health Research (NIHR) Health Technology Assessment (HTA)-funded randomised controlled trials (RCTs) published in the HTA journal were described in sufficient detail to replicate in practice.SettingRCTs published in the HTA journal.Participants98 RCTs published in the HTA journal up to March 2011. Completeness of the intervention description was assessed independently by two researchers using a checklist, which included assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…As in these previous studies, 4,6,24 we found the intervention setting/location and mode of delivery to be generally well described and descriptions of materials to be consistently lacking. The extent of missing intervention information in our sample, however, appears to be even greater, with the description of many other key components also missing from reports.…”
Section: Comparison With Other Studies Reporting On the Description Omentioning
confidence: 57%
See 3 more Smart Citations
“…As in these previous studies, 4,6,24 we found the intervention setting/location and mode of delivery to be generally well described and descriptions of materials to be consistently lacking. The extent of missing intervention information in our sample, however, appears to be even greater, with the description of many other key components also missing from reports.…”
Section: Comparison With Other Studies Reporting On the Description Omentioning
confidence: 57%
“…A complete description of this item (Item 8) was missing for almost half (47%) of the interventions in our sample compared with 10% to 25% in previous research. 6,24 This level of missing information was, however, closer to that observed in an examination of exercise interventions for breast cancer survivors, 26 with 34% of included studies failing to report on the intensity, frequency, or length of exercise sessions. Underreporting of these elements is disappointing given that the F.I.T.T principle (frequency, intensity, timing and type), along with the concepts of progression and tailoring captured in Item 9, is well established as a core methodology in exercise prescription.…”
Section: Comparison With Other Studies Reporting On the Description Omentioning
confidence: 93%
See 2 more Smart Citations
“…The extent of inadequate reporting of interventions has been investigated in a number of studies, with between 50 to 60 percent of papers missing essential elements in the description of the interventions (Glasziou, Meats, Heneghan, & Shepperd, 2008;Schroter, Glasziou, & Heneghan, 2012). Reporting of nonpharmacological interventions is typically worse than pharmacological interventions (Douet, Milne, Anstee, Habens, Young, & Wright, 2014;Glasziou et al, 2008). In a cross-sectional analysis of 137 non-pharmacological interventions, only 39% were described adequately in the primary paper, protocols or related websites (Hoffmann, Erueti, & Glasziou, 2013).…”
Section: Introductionmentioning
confidence: 99%